2013
DOI: 10.1007/s10645-013-9216-2
|View full text |Cite
|
Sign up to set email alerts
|

Unemployment of Non-Western Immigrants in the Great Recession

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…For the UK and Germany Dustmann et al (2010) find that unemployment is more strongly cyclical for immigrants than for natives, and especially for immigrants from outside the OECD. Similar results are found for Sweden in the recession of the early 1990s (Arai and Vilhelmsson, 2004) and for the Netherlands in the current recession (Cerveny and Van Ours, 2013). Partly this reflects differences in skill levels but, even within skill groups, immigrants are more vulnerable to changes in unemployment than non-immigrants.…”
Section: Who Bears the Burden Of Unemployment?supporting
confidence: 70%
“…For the UK and Germany Dustmann et al (2010) find that unemployment is more strongly cyclical for immigrants than for natives, and especially for immigrants from outside the OECD. Similar results are found for Sweden in the recession of the early 1990s (Arai and Vilhelmsson, 2004) and for the Netherlands in the current recession (Cerveny and Van Ours, 2013). Partly this reflects differences in skill levels but, even within skill groups, immigrants are more vulnerable to changes in unemployment than non-immigrants.…”
Section: Who Bears the Burden Of Unemployment?supporting
confidence: 70%
“…However, non‐Western immigrants often have a lower educational attainment and a weaker labor market position (see e.g. Cerveny and van Ours, ). The country of origin of non‐Western immigrants is related to two events in recent Dutch immigration history.…”
Section: Immigrants and Dutch Primary Schoolsmentioning
confidence: 99%
“…Neumayer (2005a), for example, found that higher levels of GDP led to higher recognition rates in European states -perhaps because they can better afford to take on the financial cost of asylum seekers -while the percent of unemployed in the state had no significant effect. However, increasing concerns over the sustainability of welfare states (Vincent 1996) as well as rising unemployment in the wake of the Great Recession (Bell and Blachflower 2011;Cervany and van Ours 2013;Hatton 2012) may have changed or increased the influence of economic factors on asylum rates in recent years. Higher levels of GDP may still contribute to higher recognition rates, but high rates of unemployment may temper them, leading to a reliance on intermediate or temporary forms of protection, or even cause the overall rates of protection to decrease.…”
Section: Destination Statesmentioning
confidence: 99%
“…To answer this question, I examine variables identified in the literature as affecting recognition rates 3 , including characteristics of the individual applicants, their states of origin, and the states in which their asylum applications were filed. Data was collected for 32 European states -the 28 members of the European Union as well as Iceland, Liechtenstein, Norway, andSwitzerland -between 2008 and2013. This analysis aims to simultaneously test the findings of earlier studies and to contribute to the limited set of studies that include individual applicant characteristics, specifically gender and age, as independent variables.…”
mentioning
confidence: 99%